A real-time hybrid testing based on shaking table and actuator for cable tray systems. (1st June 2023) - Xu, Guoshan; Zheng, Lichang; Wu, Bin; Wang, Zhen; Sun, Guoliang; Zhang, Xuezhong; Li, Dongjun; Yang, Ge; Wang, Tao
Highlights: A real-time hybrid testing based on shaking table and actuator is proposed for cable tray system. The proposed method is validated by numerical simulations. The proposed method is experimentally validated by one cable tray system. Abstract: For precisely disclosing the seismic performance of cable tray systems, one novel Real-Time Hybrid Testing based on Shaking Table and Actuator (RTHT-STA) is proposed in this paper. In the proposed method, one shaking table is used to simulate the ground motion, and one servo-hydraulic actuator controlled with displacement mode is set up on the shaking table for truly simulating the transverse shear boundary conditions between the numerical substructure and the experimental substructure of cable tray systems. The advantage of the proposed method is accurately realizing the loading requirements of high-precision large deformation on cable tray systems. The effectiveness and accuracy of the proposed method are validated by numerical simulations and experimental tests. The experimental results show that the real-time hybrid testing system is stable and reliable. The correlation coefficients between the results of the proposed method and those of the traditional shaking table tests are higher up to 91.78%. The results indicate the effectiveness and the high accuracy of the proposed RTHT-STA for cable tray systems. The RTHT-STA provides an economical and precise investigation strategy for disclosing the seismic performance of cable tray systems and may have broad application prospects in the field of communication engineering and civil engineering.